2021
DOI: 10.3389/fendo.2021.768850
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Sodium-Glucose Cotransporter 2 Inhibitors in Patients With Concurrent Type 2 Diabetes Mellitus and Non-Alcoholic Steatohepatitis: A Review of the Evidence

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most prevalent liver disease worldwide, and more than half of individuals diagnosed with type 2 diabetes concurrently present with NAFLD. There is a bidirectional pathological relationship between the two conditions, whereby NAFLD increases the risk of type 2 diabetes, and type 2 diabetes contributes to and accelerates the progression of NAFLD. Furthermore, over 30% of patients with NAFLD progress to non-alcoholic liver steatohepatitis (NASH), which then increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 91 publications
(121 reference statements)
0
9
0
Order By: Relevance
“…However, our data suggested that individuals with MAFLD or DKD should be cautious about initiating pioglitazone due to the possible risk of heart failure. In this regard, glucose-lowering drugs, including SGLT2 inhibitors or glucagon-like peptide 1 receptor agonists (GLP-1 RAs) that confer protection against major cardiovascular diseases , are promising for preventing HF in NAFLD or MAFLD [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, our data suggested that individuals with MAFLD or DKD should be cautious about initiating pioglitazone due to the possible risk of heart failure. In this regard, glucose-lowering drugs, including SGLT2 inhibitors or glucagon-like peptide 1 receptor agonists (GLP-1 RAs) that confer protection against major cardiovascular diseases , are promising for preventing HF in NAFLD or MAFLD [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the administration of SGLT2 inhibitors has proven efficacy in terms of reducing plasma levels of ALT, body weight [ 77 ], and blood pressure and improving glycated hemoglobin (HbA1c) [ 78 ], reducing risks of cardiovascular and renal diseases, all of which are factors that inhibit the progression to NASH [ 79 ]. In addition, by reducing fat mass, SGLT2 inhibitors prevent the release of inflammatory cytokines by adipocytes, thus decreasing the inflammatory effect, which is one of the main causes of NASH progression [ 80 ].…”
Section: Sglt2 Inhibitorsmentioning
confidence: 99%
“…The prevalence of NAFLD including liver steatosis and liver fibrosis in T2DM has been estimated to be more considerable 3 , 7 . According to the recent evidence, over fifty percent of individuals with T2DM concurrently have NAFLD 8 , 9 . NAFLD is substantially caused by visceral adipose tissue and insulin resistance 10 .…”
Section: Introductionmentioning
confidence: 99%